2020
DOI: 10.1007/978-981-15-0069-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Security Cafés: A Deliberative Democratic Method to Engage Citizens in Meaningful Two-Way Conversations with Security Authorities and to Gather Data

Abstract: The Security Café is a deliberation and data collection method developed for security authorities and researchers to access the opinion of the general public on issues of importance to their safety and security. It is based on the ideals of deliberative democracy, and the method derives from Citizens' Juries and World Cafés. A Security Café typically lasts for three to five hours and involves receiving information, facilitated small group discussions, and the use of idea rating sheets, or pre-and postdeliberat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The security café is an adjusted deliberative democratic method deriving from the ideals of deliberative democracy and deliberative mini-publics (Puustinen et al 2020). Deliberative democracy is a form of democracy that values discussion, reflection, and consideration over simply voting or responding to a questionnaire (e.g., Yankelovich 1991; Chambers 2003), and is often seen as an umbrella term for a wide variety of innovative deliberative democratic processes (e.g., Nabatchi 2010).…”
Section: A Security Café As a Data Collection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The security café is an adjusted deliberative democratic method deriving from the ideals of deliberative democracy and deliberative mini-publics (Puustinen et al 2020). Deliberative democracy is a form of democracy that values discussion, reflection, and consideration over simply voting or responding to a questionnaire (e.g., Yankelovich 1991; Chambers 2003), and is often seen as an umbrella term for a wide variety of innovative deliberative democratic processes (e.g., Nabatchi 2010).…”
Section: A Security Café As a Data Collection Methodsmentioning
confidence: 99%
“…A security café typically lasts for three to five hours and involves receiving information, facilitated small group deliberations, and the use of idea rating sheets. In previous projects, the security-café method has been used to involve ordinary citizens in deliberations on issues related to the domains of safety and security (e.g., asylum seeker policy and hybrid threats), and also to harvest the viewpoints of local and regional public authorities and NGO representatives on the co-creation of safety and security in Finland (see Puustinen et al 2020).…”
Section: A Security Café As a Data Collection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Security Café is a deliberation and data collection method developed for the use of security authorities and researchers to access the general public opinion on safety and security issues. It is based on the ideals of deliberative democracy, and the method derives from Citizens' Juries and World Cafés (Puustinen et al 2020). The study on Security Cafés showed that people are willing and able to participate in local security planning and information sharing (Jalava et al 2017).…”
Section: The Finnish Csm In a Nutshell: Securing The Vital Functions mentioning
confidence: 99%